Aid, fiscal policy, climate change, and growth - David Bevan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper sets out to provide an introduction to two sets of questions, and to some relevant literature that has tried to answer them. The first set of questions concern what determines growth in low-income countries, and how the answers are conditioned by the history of fiscal policy design (public capital, debt and deficit management, for example). The second (related) set of questions concerns how to design fiscal policy in face of future uncertainties over climate change, structural change, and the evolution of aid flows. The paper is intended to ask questions, rather than answer them, but at least to provide some structure within which to do this.
Keywords: F35; H11; O23; O44; 330; structural change; low-income countries; environment; public capital and public financing; Wirtschaftswachstum; Finanzpolitik; Klimawandel; Strukturwandel; Entwicklungshilfe; Niedriglohnländer